(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The progression of mental asylums mirrors the transformation of society perceptions toward mental disease, ranging from old supernatural explanations to modern psychiatric facilities based on scientific principles and human rights. This study delineates the historical evolution of mental asylums, commencing with ancient and medieval confinement practices, progressing through the founding of custodial asylums, and culminating in the reform efforts of the 18th and 19th centuries. The 20th century signified the waning of large-scale institutions and the emergence of community psychiatry, but the 21st century has ushered in contemporary psychiatric hospitals, internet mental health platforms, and international policy frameworks that emphasize human dignity and social reintegration. A historical-analytical methodology, underpinned by archival and secondary sources, is employed to investigate the evolution of asylums from prison establishments to comprehensive mental institutes. Statistical analysis indicates a decrease in institutionalization and an increase in community-based and technology-driven care. The study continues by underscoring the necessity of amalgamating historical insights with contemporary issues to formulate an inclusive future for mental health systems.